Contemporary View on the Hierarchy of Spatial and Temporal Structures: a Study of In Custody: Exploring the Hierarchy of Spatial and Temporal Structures in the Novel 'In Custody' (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In literature, there is noother device which captures imagination of the narrative in both temporal andspatial implications. Time and space are regarded as substrata of culture. Hereis an attempt to outline a contemporary view on the hierarchy of spatial andtemporal structures. The ‘conceptual primitiveness’ has been revisited throughthe study of In Custody. Marred by time and place, the protagonist movesin search of his identity. The presentation of the characters is very near tothe life in twentieth century India, ‘True to the temper of our times, thereare no heroes, no big chested ideologies, and no utopias that will providecomplete solutions to our problems’ (Das, 2002).